The Enactment of Care: Lessons Learned From a Multisector Coalition Advocating for Those Living in Senior Housing. (17th December 2021) - Sanford, Claudia; Archambault, Dennis; Waktins, Michele; Kilgore, Zach; Appel, Michael; Perry, Tam
Abstract: This presentation explores how a coalition, Senior Housing Preservation-Detroit, considered and planned for "care" in senior buildings in Detroit, Michigan. Detroit was one of the American cities affected in the early days of the pandemic; the coalition pivoted its work in creative, collaborative ways which included understanding the rapidly changing context for those living in low-income senior buildings. Older minority adults have been shown to be disproportionally affected by COVID-19; the coalition successfully advocated for testing to be brought to senior buildings (and now vaccine distribution) and addressed mask distribution and food insecurity in several senior buildings (see Archambault, Sanford and Perry, 2020). Without the long-established partnerships, "care" could not have been as coordinated, multi-sector and trusted. The presentation will discuss lessons learned that can be applied to future challenges in supporting the well-being of residents as they negotiate their residential spaces.